Exploring the Mechanism of Panax notoginseng Saponins against Alzheimer's Disease by Network Pharmacology and Experimental Validation. (30th December 2021) - Jiang, Yixuan; Li, Shanliang; Xie, Xiaoqin; Li, Hemei; Huang, Panling; Li, Bocun; Huo, Lini; Zhong, Jing; Li, Yuqing; Xia, Xing
Abstract : Background . Panax notoginseng saponins (PNS) have been used for neurodegenerative disorders such as cerebral ischemia and Alzheimer's disease (AD). Although increasing evidences show the neuron protective effects of PNS, the vital compounds and their functional targets remain elusive. To explore the potential functional ingredients of PNS for the AD treatment and their molecular mechanisms, an in vitro neuron injured model induced by A β was investigated, and the potential mechanism was predicted by network pharmacology approach and validated by molecular biology methods. Methods . Network pharmacology approach was used to reveal the relationship between ingredient-target disease and function-pathway of PNS on the treatment of AD. The active ingredients of PNS were collected from TCMSP, PubChem database, and literature mining in PubMed database. DrugBank and GeneCards database were used to predict potential targets for AD. The STRING database was performed to reveal enrichment of these target proteins, protein-protein interactions, and related pathways. Networks were visualized by utilizing Cytoscape software. The enrichment analysis was performed by the DAVID database. Finally, neuroprotective effect and predictive mechanism of PNS were investigated in an in vitro AD model established by A β 25–35 -treated PC12 cells. Results . An ingredient-target disease and function-pathway network demonstrated that 38 active ingredients were derived from PNS modulated 364 common targets shared by PNS and AD. GO and KEGG analysis, further clustering analysis, showed that mTOR signaling targets were associated with the neuroprotective effects of PNS. In A β -treated PC12 cells, PNS treatment improved neuroprotective effect, including mTOR inhibition and autophagy activation. Conclusions . Collectively, the protective effects of PNS on AD-neuron injury are related to the inhibition of mTOR and autophagy activation.